Pacing electrodes to ablate, not to pace: what settings to use to create lesions even deep in the septum. (19th May 2022) - Nedios, S; Seewoester, T; Darma, A; Dinov, B; Hildert, S; Lucas, J; Doering, M; Dagres, N; Arya, A; Hindricks, G; Bollmann, A; Richter, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Intramural septal ventricular arrhythmia remains challenging, requiring emergent technologies and experimental approaches. Although conduction system pacing (CSP) has allowed us to reach deep in the septum, ablation though pacing electrodes has not been examined yet. Purpose: To evaluate lesion creation by radiofrequency ablation (RFA) through pacing electrodes. Methods: A custom ex vivo swine model in a saline bath with an indifferent electrode was used to apply RFA with an 8 mm non-irrigated catheter (SJM, MN, USA) on the proximal end of pacing (CapSureFix 5086) or CSP-electrodes (SelectSecure 3830, Medtronic, MN, USA), screwed in perpendicularly to the slab. A generator (Ampere, SJM, MN, USA) applied RFA at varying settings (1-10 W, 1-20 sec). Lesion depth (D), width (W) and volume (V=3, 14*W2*D/4) were assessed and analyzed (SPSS 23). Results: A total of 80 lesions were used for analysis. Median RFA with 3 W over 6 sec resulted in an impedance drop from 200 to 140 Ω and a lesion of 2x3 mm or 9.4 mm3 (Figure 1). Higher energy settings caused impedance rise with abort (n=3, 4%) or charring (n=3, 4%). Compared to conventional electrodes, lesions with CSP-electrodes had similar volume (9.3±7 vs. 10.8±9 mm3, p=0.45) and width (2±0.8 vs. 2±0.7, p=0.58), but more depth (2.6±0.5 vs. 3±0.6, p=0.0.01). Regression analysis showed final-impedance (FI), power and duration (WS=W*Sec) as independent predictors of lesion volume (V=4.7WS-4.1WS2+4.5FI-4, p<0.001). Conclusions: Effective ablation through pacing electrodes is possible, but lesion size is limited and low-power settings are necessary. Using CSP-electrodes for effective intramural lesions is possibly a new tool for septal arrhythmias. Further in vivo studies are warranted and bailout use should be considered.